ANALISA YURIDIS TERHADAP PENERBITAN FAKTUR FIKTIF - Sandy Sulistiono; Tanudjaja Tanudjaja (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The embodiment of the Indonesian State in providing prosperity to its nation as mandated in the 1945 Constitution of the Republic of Indonesia is by collecting taxes which are used to provide support for national development. However, along the way, collecting taxes from taxpayers is not easy because the existing tax compliance is still low. So that fraudulent acts emerge which lead to criminal acts, one of which is the issuance and/or use of tax invoices that are not in accordance with ongoing transactions. Therefore, this research will examine the criminal liability of corporations as users of fictitious tax invoices in tax crimes and how judges consider fictitious invoices in cases in the Semarang High Court Decision Number 258/PID/2021/PT.SMR. Because this research is legal research, the approach used is a conceptual approach which is based on the concept of tax development and tax crime supported by a statutory approach such as being based on the Director General of Taxes' regulations and general tax provisions.